Impact of Lowland Rainforest Transformation on Diversity and Composition of Soil Prokaryotic Communities in Sumatra (Indonesia) - Schneider, Dominik; Engelhaupt, Martin; Allen, Kara; Kurniawan, Syahrul; Krashevska, Valentyna; Heinemann, Melanie; Nacke, Heiko; Wijayanti, Marini; Meryandini, Anja; Corre, Marife D.; Scheu, Stefan; Daniel, Rolf (Frontiers in Microbiology, 2015)
Prokaryotes are the most abundant and diverse group of microorganisms in soil and mediate virtually all biogeochemical cycles in terrestrial ecosystems. Thereby, they influence aboveground plant productivity and diversity. In this study, the impact of rainforest transformation to intensively managed cash crop systems on soil prokaryotic communities was investigated. The studied managed land use system comprised rubber agroforests (jungle rubber), rubber plantation and oil plantations within two Indonesian landscapes Bukit Duabelas and Harapan. Soil prokaryotic community composition and diversity were assessed by pyrotag sequencing of bacterial and archaeal 16S rRNA genes. The curated dataset contained 20,494 bacterial and 1,762 archaeal Operational Taxonomic Units at species level (97% genetic identity). Analysis revealed changes in indigenous taxon-specific patterns of soil prokaryotic communities accompanying lowland rainforest transformation to jungle rubber, and intensively managed rubber and oil palm plantations. Distinct clustering of the rainforest soil communities indicated that these are different from the communities in the studied managed land use systems. The predominant bacterial taxa in all investigated soils were Acidobacteria, Actinobacteria, Alphaproteobacteria, Betaproteobacteria, and Gammaproteobacteria. Overall, the bacterial community shifted from proteobacterial groups in rainforest soils to Acidobacteria in managed soils. The archaeal soil communities were mainly represented by Thaumarchaeota and Euryarchaeota. Members of the Terrestrial Group and South African Gold Mine Group 1 (Thaumarchaeota) dominated in the rainforest and members of Thermoplasmata in the managed land use systems. The alpha and beta diversity of the soil prokaryotic communities was higher in managed land use systems than in rainforest. In the case of bacteria, this was related to soil characteristics such as pH value, exchangeable Ca and Fe content, C to N ratio, and extractable P content. Archaeal community composition and diversity were correlated to pH value, exchangeable Fe content, water content, and total N. The distribution of bacterial and archaeal taxa involved in biological N cycle indicated functional shifts of the cycle during conversion of rainforest to plantations.